Neuropathological Mechanisms of Mild Traumatic Brain Injury: A Perspective From Multimodal Magnetic Resonance Imaging - Liu, Yin; Lu, Liyan; Li, Fengfang; Chen, Yu-Chen (Frontiers in Neuroscience, 2022)
Mild traumatic brain injury (mTBI) accounts for more than 80% of the total number of TBI cases. The mechanism of injury for patients with mTBI has a variety of neuropathological processes. However, the underlying neurophysiological mechanism of the mTBI is unclear, which affects the early diagnosis, treatment decision-making and prognosis evaluation. More and more multimodal magnetic resonance imaging (MRI) techniques have been applied for the diagnosis of mTBI, including functional magnetic resonance imaging (fMRI), arterial spin labeling (ASL) perfusion imaging, susceptibility-weighted imaging (SWI), diffusion MRI (dMRI). Various imaging techniques require to be used in combination for neuroimaging examinations for mTBI patients. The understanding of the neuropathological mechanism of mTBI has been improved based on different angles. In this review, we will summarize the application of these aforementioned multimodal MRI technique in mTBI and evaluate its benefits and drawbacks.